How to interpret observations of neutron-star mergers?. (October 2020) - Just, Oliver; Bauswein, Andreas; Goriely, Stephane; Ito, Hirotaka; Janka, Hans-Thomas; Nagataki, Shigehiro
Abstract: The recent first multi-messenger observation of a neutron-star merger, GW170817 and its electromagnetic counterparts, has sparked tremendous excitement particularly because long-standing questions related to heavy-element nucleosynthesis and the nuclear equation of state could finally be tested with unprecedented capabilities. This proceedings article briefly reviews the main observation channels of neutron-star mergers and how those can be used to obtain insight about questions related to nucleosynthesis and the nuclear equation of state.